2015
DOI: 10.1111/jfs.12197
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and Physicochemical Quality Changes in Frankfurters Made from Jumbo Squid (Dosidicus gigas) Mantle Muscle in the Presence and Absence of a Natural Antimicrobial Agent

Abstract: This study aimed to evaluate the effect of a natural antimicrobial agent (Pronat) on selected quality indicators during the shelf life of vacuum-packed frankfurters made from jumbo squid (Dosidicus gigas) muscle. Frankfurters with and without Pronat (0.1%) were vacuum-packed and stored at 2-4C for up to 28 days. The physicochemical parameters (water loss, pH, thiobarbituric acid value, peroxide value, moisture, texture [texture profile analysis and sharing force], folding test performance, water-holding capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…CSPSP is a sterilized product, with no coliforms detected per gram, thus adhering to the sanitary indicator bacteria standards outlined for age-friendly foods in the Food Code [31]. Carrero-Colon and Turco [48], along with Ramírez-Suárez et al [15], have previously highlighted coliform groups as indicators of fecal substances in food and their vulnerability to heat. Consequently, the heating conditions employed in this study (90 ± 5 • C, 30 min) for CSPSP were deemed adequate for sterilizing intestinal bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CSPSP is a sterilized product, with no coliforms detected per gram, thus adhering to the sanitary indicator bacteria standards outlined for age-friendly foods in the Food Code [31]. Carrero-Colon and Turco [48], along with Ramírez-Suárez et al [15], have previously highlighted coliform groups as indicators of fecal substances in food and their vulnerability to heat. Consequently, the heating conditions employed in this study (90 ± 5 • C, 30 min) for CSPSP were deemed adequate for sterilizing intestinal bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fish-based sausages, various studies have explored sausages made from pork and frozen pollock [8], chicken breast and pollock meat [9], mackerel meat [10], rainbow trout fish [11], catfish meat [12], clam meat [13], octopuses [14], and jumbo squid (Dosidicus gigas) [15], as well as sausages incorporating the emulsion of Argentina squid (Illex argentines) [16].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it met all the standards presented in Korea's Food Code [5], indicating that it has hygiene indicators for supplying safe food to elderly consumers. Ramírez-Suárez et al [46] reported the indicators of most heat-vulnerable bacteria that are present in food. Thus, the heating conditions (121 • C, 20 min) applied to the LOJP developed in this study were confirmed to be suitable conditions for sterilizing the LOJP.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrophysical exploration of cephalopods is therefore limited, but a few examples include the investigation of L. forbesii [ 32 , 54 , 114 ]. Other studies involving cephalopods in a culinary context investigated (commercial) food preparations, ranging from frankfurters prepared from the mantle of Dosidicus gigas [ 66 ], ready-to-eat Indian squid ( L. dauvacelli Orbigny) masala [ 76 ], and battered and fried squid rings [ 47 ].…”
Section: Cephalopod Gastronomy and Gastrophysicsmentioning
confidence: 99%